Proteomic and in silico analyses of dextran synthesis influence on Leuconostoc lactis AV1n adaptation to temperature change - Besrour-Aouam, Norhane; de Los Rios, Vivian; Hernández-Alcántara, Annel M.; Mohedano, Mᵃ Luz; Najjari, Afef; López, Paloma; Ouzari, Hadda-Imene (Frontiers in Microbiology, 2023)
Leuconostoc lactis is found in vegetables, fruits, and meat and is used by the food industry in the preparation of dairy products, wines and sugars. We have previously demonstrated, that the dextransucrase (DsrLL) of Lc. lactis AV1n produces a high molecular weight dextran from sucrose, indicating its potential use as a dextran forming starter culture. We have also shown that this bacterium was able to produce 10-fold higher levels of dextran at 20 °C than at 37 °C, at the former temperature accompanied by an increase of dsrLL gene expression. However, the general physiological response of Lc. lactis AV1n to cold temperature in the presence of sucrose, leading to an increased production of dextran has not been yet investigated. Therefore, we have here used a quantitative proteomics approach to investigate the cold temperature-induced changes in the proteomic profile of this strain in comparison to its proteomic response at 37 °C. In total, 337 proteins were found to be differentially expressed at the applied significance criteria (adjusted p-value ≤ 0.05, FDR 5%, and with a fold change ≥ 1.5 or ≤ 0.67)) with 204 proteins overexpressed, among which 13% were involved in protein as well as cell wall, and envelope component biosynthesis including DsrLL. Proteins implicated in cold stress were expressed at high level at 20 °C and possibly play a role in the up-regulation of DsrLL allowing efficient synthesis of the protein essential for its adaptation to cold. Post-transcriptional regulation of DsrLL expression also seems to take place through the interplay of exonucleases and endonucleases overexpressed at 20 °C, that would influence the half-life of the dsrLL transcript. Furthermore, the mechanism of cold resistance of Lc. lactis AV1n seems to be also based on energy saving through a decrease in growth rate mediated by a decrease in carbohydrate metabolism and its orientation towards the production pathways for storage molecules. Thus, this better understanding of the responses to low temperature and mechanisms for environmental adaptation of Lc. lactis could be exploited for industrial use of strains belonging to this species.